Molecular systematics of the heteronemertean genus Dushia (Nemertea, Pilidiophora), with descriptions of D. wijnhoffae sp. nov. and D. nigra species complex comb. nov. - Hookabe, Natsumi; Schwartz, Megan L.; Kajihara, Hiroshi; Norenburg, Jon L. (Zootaxa, 2019)
The heteronemertean genus Dushia Corrêa, 1963 was established for what was identified as D. atra (Girard, 1851) (originally Meckelia atra) based on material from littoral, shallow waters in Curaçao, while the nominal species Meckelia atra was originally described from deep water off Florida Cape. In this paper, we conclude that the type species for Dushia has been misidentified. Based on specimens from the Caribbean, we establish D. wijnhoffae Schwartz & Norenburg sp. nov. to represent the true identity of the genus, according to Article 70.3.2 of the International Code of Zoological Nomenclature; Meckelia atra should be regarded as a nomen dubium. While the genus has remained monotypic since its establishment, our molecular analysis discovered a second member—or rather a group of members—from the West Pacific. This ‘group of members’, herein termed Dushia nigra (Stimpson, 1855) species complex comb. nov., involves i) at least two genetically separated biological entities, 0.136–0.148 (p-distance) and 0.152–0.168 (K2P) apart in terms of 513-bp COI sequences, which we interpret as likely to represent cryptic species, ii) three color forms, orange, brown, and black, with the last one occurring most frequently, and iii) four nominal species, Meckelia nigra Stimpson, 1855 (now Cerebratulus niger), Meckelia rubella Stimpson, 1855 (now Cerebratulus rubellus), Micrura formosana Yamaoka, 1939, and Micrura japonica Iwata, 1952. At present, however, we have no objective ground as to which of the four potentially available names (i.e., formosana, japonica, nigra, and rubella) should be allotted to the two cryptic species discovered in the analysis, because i) a single locality can harbor two cryptic species, ii) a single cryptic species may contain three different color morphs (i.e., orange, brown, black), and iii) no data from the type localities for these four nominal species are available at the moment. Our multi-locus analysis of heteronemerteans—for which 16S rRNA, COI, 18S rRNA, 28S rRNA, histone H3 genes are available in public databases—shows that Dushia wijnhoffae sp. nov. and Dushia nigra species complex comb. nov. form a clade, which is closely related to Gorgonorhynchus albocinctus Kajihara, 2015 and an undetermined heteronemertean that has been misidentified as Cerebratulus leucopsis (Coe, 1901). Members of Dushia thus show a vicariant Caribbean–West-Pacific distribution, indicating that the lineage predates the rise of the Isthmus of Panama.